Perceptions of the coast and managing coastal change in Western Newfoundland : a case study of Norris Point : interpreting the views of multiple stakeholders in a small coastal community - Blackwood, April, 1992- (2017)
Nestled along the coast of the Canadian province of Newfoundland and Labrador are hundreds of small communities. Like coasts all over the world, the coastlines of these communities are changing due to the natural actions of the ocean through winds, waves, and tides in combination with anthropogenic actions through development. These changes have an effect on the people that call these coastal communities home and these changes need to be managed. Understanding the perspectives of the people within the community can contribute to the development of a holistic and sustainable coastal management plan. This study gathered local resident perceptions in regards to how they value the coast, and understand the coast and coastal processes. This understanding was used to see how coastal management and planning at the local level can be supported by understanding local concerns. A case study of Norris Point, Newfoundland and Labrador was used. Mixed- methods were used including site observations, discussion with experts, casual conversation and semi-structured interviews with local residents, and review of municipal town planning documents. Results of the study express that participants were aware of the coastal change that was taking place in the community. Overall, the perceptions gained from the discussions with local residents corresponded with the information gained from informed individuals. Their local knowledge can contribute to the development of a coastal management plan for Norris Point that will be socially accepted. This study only looked at a small sample size, and future research should be carried out to deepen the understanding of the connection between local resident perceptions and successful coastal management. Coastal managers that look deeper into local resident perceptions and values can create opportunities for reviving cultural feelings towards the coast and building on these feelings to create more effective management strategies.